Telomere attrition occurs during ex vivo expansion of human dental pulp stem cells - Mokry, Jaroslav; Soukup, Tomas; Micuda, Stanislav; Karbanova, Jana; Visek, Benjamin; Brcakova, Eva; Suchanek, Jakub; Bouchal, Jan; Vokurkova, Doris; Ivancakova, Romana (Journal of biomedicine & biotechnology, 2010)
We provide a detailed characteristic of stem cells isolated and expanded from the human dental pulp. Dental pulp stem cells express mesenchymal cell markers STRO-1, vimentin, CD29, CD44, CD73, CD90, CD166, and stem cell markers Sox2, nestin, and nucleostemin. They are multipotent as shown by their osteogenic and chondrogenic potential. We measured relative telomere length in 11 dental pulp stem cell lines at different passages by quantitative real-time PCR. Despite their large proliferative capacity, stable viability, phenotype, and genotype over prolonged cultivation, human dental pulp stem cells suffer from progressive telomere shortening over time they replicate in vitro. Relative telomere length (T/S) was inversely correlated with cumulative doubling time. Our findings indicate that excessive ex vivo expansion of adult stem cells should be reduced at minimum to avoid detrimental effects on telomere maintenance and measurement of telomere length should become a standard when certificating the status and replicative age of stem cells prior therapeutic applications.
Keywords: kinetika; kultivované buňky; zubní dřeň; průtoková cytometrie; chondrogeneze; Multipotent Stem Cells; DNA; Time Factors; mladiství; imunohistochemie; mužské pohlaví; Reference Standards; Dental Pulp; Cell Proliferation; referenční standardy; mladý dospělý; Adult; počet buněk; Osteogenesis; Flow Cytometry; Cells, Cultured; Immunohistochemistry; Young Adult; osteogeneze; ženské pohlaví; Microscopy, Phase-Contrast; multipotentní kmenové buňky; Chondrogenesis; Humans; Antigens, CD; mikroskopie fázově kontrastní; časové faktory; Kinetics; analýza kolonii tvořících jednotek; proliferace buněk; telomery; Stem Cells; Telomere; Colony-Forming Units Assay; dospělí; kmenové buňky; Cell Count; Female; Adolescent; CD antigeny; lidé; Male